A Validated Stability-Indicating RP-HPLC Method for the Simultaneous Determination of Tenofovir, Emtricitabine, and a Efavirenz and Statistical Approach to Determine the Effect of Variables. (28th January 2013) - Devrukhakar, Prashant S.; Borkar, Roshan; Shastri, Nalini; Surendranath, K. V.
Abstract : A simple, rapid, and stability-indicating RP-HPLC method for a combination of tenofovir disoproxil fumarate (TDF), emtricitabine (FTC), and efavirenz (EFV) was developed and validated with the help of a suitable statistical software as an application tool for the quality by design. The drugs individually, and in combination, were subjected to forced degradation (thermal, photolytic, hydrolytic, and oxidative stress conditions) and accelerated stability studies (40 ± 1°C/75 ± 3% RH for three months). Successful separation of combined drugs from degradation products was achieved by gradient elution on a reverse-phase C18 column, using a mobile phase containing phosphate buffer (pH 3.5): acetonitrile at 1.5 mL min −1 flow rate, detection wavelength 256 nm, column oven temperature 25°C, and injection volume 10 μ L. Linearity was established in the range of 20–300 μ g mL −1, 24.5–367.5 μ g mL −1 and 60–900 μ g mL −1 for FTC, TDF, and EFV, respectively. The method was successfully applied for quantifying the drugs in marketed dosage forms and on stability samples.